2011
DOI: 10.1007/s00330-011-2350-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterisation of soft tissue tumours by 1.5-T proton MR spectroscopy

Abstract: • 1H-MRS may allow differentiation between benign and malignant soft tissue lesions • Absence of choline peak is highly predictive of benign soft tissue lesions • Malignant tumours with a mitotic index >2/10 HPF had a positive choline peak • A choline peak may still be identified in some benign tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…MRS is a technique that is used to noninvasively detect and distinguish metabolite activity in a tissue of interest, such as a soft tissue tumor, based on the intrinsic resonant frequencies of various metabolites, and analyze its biochemical composition . MRS enables the detection of metabolic markers of malignancy, including the trimethyl aluminium (TMA) compounds, which present as a composite spectral resonance consisting of free choline, phosphocholine, and glycerophosphocholine; TMA is typically elevated in malignancies, including malignant soft tissue tumors.…”
Section: Quantitative Mri Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…MRS is a technique that is used to noninvasively detect and distinguish metabolite activity in a tissue of interest, such as a soft tissue tumor, based on the intrinsic resonant frequencies of various metabolites, and analyze its biochemical composition . MRS enables the detection of metabolic markers of malignancy, including the trimethyl aluminium (TMA) compounds, which present as a composite spectral resonance consisting of free choline, phosphocholine, and glycerophosphocholine; TMA is typically elevated in malignancies, including malignant soft tissue tumors.…”
Section: Quantitative Mri Biomarkersmentioning
confidence: 99%
“…However, qualitative MRS assessment is limited in its reproducibility and generalizability in a clinical setting. Prior qualitative investigations of 1 H‐MRS reported high sensitivities (88–92%) and relatively lower specificities (57–82%) for the characterization of soft tissue masses . For example, the qualitative presence of a total choline peak has been described in 50% of benign PNSTs, making the qualitative approach to MRS data less useful.…”
Section: Quantitative Mri Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of choline peak is highly predictive of benign soft tissue lesions as shown by Russo et al (75) using SVS and long TE. Previously, Subhawong et al (76) revealed that a discrete choline peak had 88% sensitivity and 68% specificity in detection of malignant musculoskeletal lesions (Fig.…”
Section: Soft-tissue Tumorsmentioning
confidence: 88%
“…The ratio of the sum of the citrate and choline peaks to the citrate peak can differentiate prostate cancer from normal parenchyma (43). MRI is the most accurate imaging investigation for evaluating soft tissue tumors (44). Preliminary studies have shown that 1H-MRS using 1.5 or 3 T MR equipment is capable of discriminating between malignant and benign soft tissue tumors (45,46).…”
mentioning
confidence: 99%